Unholy magic - Kane, Stacia; Copyright Paperback Collection (Library of Congress) (New York Del Rey/Ballantine, 2010)
For Chess Putnam, finding herself near-fatally poisoned by a con psychic and then stopping a murderous ghost is just another day on the job. As an agent of the Church of Real Truth, Chess must expose those looking to profit from the world's unpleasant
1
Keywords: Paranormal fiction; Witches -- Fiction